Dengue Virus Nonstructural Protein NS5 Induces Interleukin-8 Transcription and Secretion - Medin, Carey L. (American Society for Microbiology, 2005)
Elevated circulating levels of chemokines have been reported in patients with dengue fever and are proposed to contribute to the pathogenesis of dengue disease. To establish in vitro models for chemokine induction by dengue 2 virus (DEN2V), we studied a variety of human cell lines and primary cells. DEN2V infection of HepG2 and primary dendritic cells induced the production of interleukin-8 (IL-8), RANTES, MIP-1α, and MIP-1β, whereas only IL-8 and RANTES were induced following dengue virus infection of HEK293 cells. Chemokine secretion was accompanied by an increase in steady-state mRNA levels. No chemokine induction was observed in HEK293 cells treated with poly(I:C) or alpha interferon, suggesting a direct effect of virus infection. To determine the mechanism(s) involved in the induction of chemokine production by DEN2V, individual dengue virus genes were cloned into plasmids and expressed in HEK293 cells. Transfection of a plasmid expressing NS5 or a dengue virus replicon induced IL-8 gene expression and secretion. RANTES expression was not induced under these conditions, however. Reporter assays showed that IL-8 induction by NS5 was principally through CAAT/enhancer binding protein, whereas DEN2V infection also induced NF-κB. These results indicate a role for the dengue virus NS5 protein in the induction of IL-8 by DEN2V infection. Recruitment and activation of potential target cells to sites of DEN2V replication by virus-induced chemokine production may contribute to viral replication as well as to the inflammatory components of dengue virus disease.